Bilberry Supplementation after Myocardial Infarction Decreases Microvesicles in Blood and Affects Endothelial Vesiculation. Issue 20 (10th September 2020) - Bryl‐Górecka, Paulina; Sathanoori, Ramasri; Arevström, Lilith; Landberg, Rikard; Bergh, Cecilia; Evander, Mikael; Olde, Björn; Laurell, Thomas; Fröbert, Ole; Erlinge, David
Abstract : Scope: Diet rich in bilberries is considered cardioprotective, but the mechanisms of action are poorly understood. Cardiovascular disease is characterized by increased proatherogenic status and high levels of circulating microvesicles (MVs). In an open‐label study patients with myocardial infarction receive an 8 week dietary supplementation with bilberry extract (BE). The effect of BE on patient MV levels and its influence on endothelial vesiculation in vitro is investigated. Methods and results: MVs are captured with acoustic trapping and platelet‐derived MVs (PMVs), as well as endothelial‐derived MVs (EMVs) are quantified with flow cytometry. The in vitro effect of BE on endothelial extracellular vesicle (EV) release is examined using endothelial cells and calcein staining. The mechanisms of BE influence on vesiculation pathways are studied by Western blot and qRT‐PCR. Supplementation with BE decreased both PMVs and EMVs. Furthermore, BE reduced endothelial EV release, Akt phosphorylation, and vesiculation‐related gene transcription. It also protects the cells from P2X7 ‐induced EV release and increase in vesiculation‐related gene expression. Conclusion: BE supplementation improves the MV profile in patient blood and reduces endothelial vesiculation through several molecular mechanisms related to the P2X7 receptor. The findings provide new insight into the cardioprotective effects of bilberries. Abstract : Bilberries are considered beneficial in cardiovascular disease (CVD). In this study, patients with myocardial infarction receive an 8 week dietary supplementation with bilberry extract (BE). While CVD patients are characterized by high levels of circulating microvesicles (MVs), BE supplementation improves MV profile in patient blood by reducing the endothelial vesiculation through molecular mechanisms related to P2X7 receptor.